Surgical treatment of cardiac metastatic melanoma - Robert Kwinta; Katarzyna Kopcik (Polish Journal of Thoracic and Cardiovascular Surgery)
Melanoma is an aggressive neoplasm mainly affecting the skin. It has a predisposition to metastasis and it presents the highest propensity to spread to the heart, mostly through the hematologic route. Cardiac metastases frequently remain asymptomatic, even though the metastatic process to other organs is described as an advanced stage of the melanoma. Treatment methods include conservative and surgical management. Surgeries should be preferably performed at the early stages of the disease, when physicians can achieve total resections with clear margins. In some cases palliative procedures are also implemented. In 26 patients analyzed in this review, eleven cases presented favorable results of the surgery. In majority of the patients the diffuse metastatic disease led to their decease despite the surgery.